Desempenho de um sistema embarcado para medição de índice de vegetação da diferença normalizada utilizando LED ou TSL 2561 - Silva Filho, Armando da (2019)
The Normalized Difference Vegetation Index (NDVI) is widely used to characterize different vegetation types and phenological stages under different water and nutritional conditions. Several sensor elements can be used for the development of an NDVI measuring instrument. The objective of this study was to develop an embedded NDVI measurement system using two different sensor types, using photoconductor mode polarized LEDs to function as sensors or the TSL 2561 digital light sensor. A homogeneous NaCl surface was used in the reflectance calibration, NDVI measurements were obtained on water, NaCl, grass without water restriction and straw surfaces. The data obtained demonstrated high selectivity of the LEDs and partial selectivity of the TSL 2561 sensor. Static tests occurred simultaneously with both types of sensors and indicated that both types of sensors were suitable for reflectance measurements and NDVI determination with a correlation above. 95% between the sensors.